2020
DOI: 10.3390/mi11050495
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Nanofabrication and Intracellular Raman Imaging of Living Cells with Functionalized AFM Probes

Abstract: Atomic force microscopy (AFM) is an effective platform for in vitro manipulation and analysis of living cells in medical and biological sciences. To introduce additional new features and functionalities into a conventional AFM system, we investigated the photocatalytic nanofabrication and intracellular Raman imaging of living cells by employing functionalized AFM probes. Herein, we investigated the effect of indentation speed on the cell membrane perforation of living HeLa cells based on highly localized photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Probe geometry-forward, backward, side angles, and tip height-are also parameters that affect scanning resolution and limit the maximum detectable roughness of the sample surface. Moreover, tips could be coated with various materials to extend their application field [50].…”
Section: Cantileversmentioning
confidence: 99%
“…Probe geometry-forward, backward, side angles, and tip height-are also parameters that affect scanning resolution and limit the maximum detectable roughness of the sample surface. Moreover, tips could be coated with various materials to extend their application field [50].…”
Section: Cantileversmentioning
confidence: 99%
“…They also looked at the potential for visualizing cells using TERS. This imaging is functionalized by using silver nanoparticles in a home-built Raman system combined with an inverted microscope through AFM probes, which successfully demonstrated that TERS imaging is capable of visualizing noticeably different features in the Raman spectrum between the nucleus and cytoplasm of a single living cell and of analyzing the dynamic behavior of biomolecules in living cells ( Shibata et al, 2020 ).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Crucially, scientists have shown that the viability of the cell membrane is very high (about 100%) after the AFM tip penetrates the cell membrane. The method has significant potential for future use in studies where it is necessary to investigate the various organelles and biomolecules within the cell [75].…”
Section: Therapeutic Drug Monitoring (Tdm)mentioning
confidence: 99%